2010
DOI: 10.1037/a0018212
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a strategy-based intervention on the comprehension and strategy use of struggling adolescent readers.

Abstract: This study examines the impact of the Learning Strategies Curriculum (LSC), an adolescent reading intervention program, on 6th-and 9th-grade students' reading comprehension and strategy use. Using a randomized treatment-control group design, the study compared student outcomes for these constructs for 365 students who received daily instruction in 6 LSC strategies and 290 students who did not receive intervention instruction. After 1 school year, 6th-grade students who received intervention instruction signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(38 citation statements)
references
References 58 publications
(91 reference statements)
1
34
0
3
Order By: Relevance
“…While other research (e.g., Cantrell et al, 2013;Cantrell et al, 2010;Feldman et al, 2012;Simmons et al, 2014) that students who completed more of the workbook made greater gains from pretest to posttest, with effect sizes ranging from 0.08 to 0.35 (Kim et al, 2016). This suggests that students' completion of comprehension workbooks prepared them to achieve on standardized tests, and thus that workbook completion serves as an adequate proxy for literacy gains.…”
Section: Coaching Implementation and Outcomesmentioning
confidence: 87%
See 3 more Smart Citations
“…While other research (e.g., Cantrell et al, 2013;Cantrell et al, 2010;Feldman et al, 2012;Simmons et al, 2014) that students who completed more of the workbook made greater gains from pretest to posttest, with effect sizes ranging from 0.08 to 0.35 (Kim et al, 2016). This suggests that students' completion of comprehension workbooks prepared them to achieve on standardized tests, and thus that workbook completion serves as an adequate proxy for literacy gains.…”
Section: Coaching Implementation and Outcomesmentioning
confidence: 87%
“…Third, the vast majority of intervention research is short-term, collecting data in the first year of implementation (e.g., Benner et al, 2011;Cantrell et al, 2013;Cantrell et al, 2010;Faggella-Luby & Wardwell, 2011;Graves et al, 2011;Lang et al, 2009;Simmons et al, 2014;Solís et al, 2015;Vaughn et al, 2011). Therefore, these studies examine teachers' practice while teachers are still in the process of learning a new curriculum or instructional approach.…”
Section: The Present Studymentioning
confidence: 99%
See 2 more Smart Citations
“…With regards the other three studies reported in Table 2 ( Cantrell et al, 2010;Vaughn et al, 2011;Vaughn et al, 2013) it is noteworthy that all produced similar (low) effect sizes on reading comprehension outcomes. The intervention reported by Cantrell et al was intensive and delivered for 50 -60 minutes per day over the course of a year.…”
Section: Discussionmentioning
confidence: 99%